Post-operative rehabilitation of displaced-proximal radius fracture: a case study - Sharma, Ridham; Sikka, Gitanjali; Majok, Aarti (International Journal of Research in Medical Sciences, 2022)
Proximal radial fractures typically occur after a fall on the outstretched hand. Elbow trauma is usually followed by post-traumatic elbow stiffness, which has been recognized as a major cause of functional impairment. A stiff elbow restricts patient’s ability to position hand in space required, for desired use of the upper extremities during activity of daily living. The goal of rehabilitation, post-traumatic elbow stiffness is to restore functional arc of motion. The patient treatment should be designed depending on the severity, type and time course of the arthrofibrosis. Since, there is no universally recognized treatment algorithm, treatment must be personalized/customized and stipulated through a shared decision-making process with each patient. Fourty four-year female was diagnosed with post – operative elbow stiffness following a displaced proximal one-third of radius fracture (right side). The patient had decreased muscle strength and limited shoulder, elbow and wrist range of motion, hypersensitivity around the scar and wrist and elbow pain. Progressive multi-treatment rehabilitation approach was given to the patient. Physical therapy intervention improved range of motion, strength, decreased hypersensitivity and pain of the patient as well as aided in quick recovery from stiff elbow.